2012
DOI: 10.1152/ajpheart.00257.2011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of hexarelin attenuates cardiac fibrosis in the spontaneously hypertensive rat

Abstract: Cardiac fibrosis is a hallmark of heart disease and plays a vital role in cardiac remodeling during heart diseases, including hypertensive heart disease. Hexarelin is one of a series of synthetic growth hormone secretagogues (GHSs) possessing a variety of cardiovascular effects via action on GHS receptors (GHS-Rs). However, the role of hexarelin in cardiac fibrosis in vivo has not yet been investigated. In the present study, spontaneously hypertensive rats (SHRs) were treated with hexarelin alone or in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
5
21
1
Order By: Relevance
“…Although [D-Lys3]-GHRP-6 has been suggested to exert activities such as stimulation of calcium increase (15), decrease in food intake (1), and reduction of alcohol intake in mice (24), it is unlikely that [D-Lys3]-GHRP-6 would have beneficial effects on the doxorubicin-treated heart. Nonetheless, [D-Lys3]-GHRP-6 has been reported to abolish the antifibrotic effect of hexarelin on interstitial and perivascular fibrosis in the heart of spontaneously hypertensive rats (58), whereas the decrease in cardiac fibrosis induced by desacyl ghrelin in the doxorubicin-treated heart in this study was not found to be abolished by [D-Lys3]-GHRP-6 (Fig. 2, A and B).…”
Section: Discussioncontrasting
confidence: 55%
“…Although [D-Lys3]-GHRP-6 has been suggested to exert activities such as stimulation of calcium increase (15), decrease in food intake (1), and reduction of alcohol intake in mice (24), it is unlikely that [D-Lys3]-GHRP-6 would have beneficial effects on the doxorubicin-treated heart. Nonetheless, [D-Lys3]-GHRP-6 has been reported to abolish the antifibrotic effect of hexarelin on interstitial and perivascular fibrosis in the heart of spontaneously hypertensive rats (58), whereas the decrease in cardiac fibrosis induced by desacyl ghrelin in the doxorubicin-treated heart in this study was not found to be abolished by [D-Lys3]-GHRP-6 (Fig. 2, A and B).…”
Section: Discussioncontrasting
confidence: 55%
“…So, our data demonstrate that hexarelin reduces cardiac fibrosis in SHRs, perhaps by decreasing collagen synthesis and accelerating collagen degradation [168].…”
Section: Ghrelin and Hexarelin Promote Mitochondrial Activity And Biosupporting
confidence: 50%
“…weeks from an age of 16 weeks significantly reduced cardiac fibrosis in SHRs by decreasing interstitial and perivascular myocardial collagen deposition and myocardial hydroxyproline content and reducing mRNA and protein expression of collagen I and III in SHR hearts [168].…”
Section: Ghrelin and Hexarelin Promote Mitochondrial Activity And Biomentioning
confidence: 84%
“…For example, the regulatory role of growth hormone secretagogues (GHSs) and their receptors (GHSR), a newly found branch of the endocrine system, on the circadian clock is still elusive. GHSs are known to have effects on many physiological activities, including pituitary hormone secretion, pancreatic endocrine, gastric acid secretion, regulation of appetite, energy metabolism, and cardiovascular functions (6,13,16,33,46,47). Some investigators reported that GHSs could also influence the circadian rhythm and sleeping, but their findings are inconsistent or even contradictory.…”
mentioning
confidence: 99%